Faktor Pendukung dan Penghambat Implementasi Peraturan Izin Usaha Toko Modern Minimarket Waralaba/Cabang di Kecamatan Depok terkait Perda Kab.Sleman No.18 tahun 2012 tentang Perizinan Pusat Perbelanjaan dan Toko Modern - Otniel Handityasa P; Hartuti Purnaweni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The implementation of Sleman District regional regulation Number 18 2012 about Shopping Centers and Modern Stores Licensing for minimarket franchise or branch in Depok Districts did not go according to the rules. This study aims to determine the implementation of modern shop licensing regulations (modern store business license) in Depok Districts as well as inhibiting factors and supporting factors of the policy implementation. The research shows that the implementation of the policy of modern store business license in Depok Districts did not comply the aspects of the regulation including aspect of the business location, social aspects, aspects of partnerships with SMEs, and aspects of the use of local labor. This happened because of weak sanctions, lack of budget for the supervision and development, and the communications were not intensive between the authorities that implementing the policy with managers of modern store, and also the policy environment was not conducive. Based on these concerns, there should be an efforts starting from increasing the budget, giving more sanctions to modern stores (minimarket franchise or branch) that do not have licenses, and improve the supervision and development.